Efficacy and safety of Danhong injection for treating myocardial infarction: a systematic review and meta-analysis of randomized controlled trials - Yang, Shiyi; Wang, Yin; Shen, Hailiang; Chen, Tianhang; Du, Haixia (Frontiers in Pharmacology, 2024)
Objective Danhong injection (DHI) is widely used in the treatment of myocardial infarction (MI). We aimed to systematically review the efficacy and safety of DHI in a randomized controlled experiment on MI. Methods We searched the randomized controlled trials (RCTs) of DHI for MI published before 2 April 2023 in China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), Wanfang database, China Science and Technology Journal Database (VIP), PubMed, Web of Science, Cochrance Library, and Embase databases. The methodological quality of the included studies was evaluated using the Cochrane Handbook 5.3 criteria using the RevMan software, and meta-analysis was performed and a forest map was drawn. Results A total of 38 trials included 3877 patients, including 2022 cases in the DHI treatment group and 1855 cases in the control group. Meta-analysis showed that the total effective rate (RR = 1.18%, 95% CI [1.14–1.12]) during treatment with DHI was higher than that of the control group. The prevalence of cardiac arrhythmia (RR = 0.55%, 95% CI [0.46–0.65]) was lower than that of the control group. The incidence of heart rate failure (RR = 0.45%, 95% CI [0.30–0.70]) was lower than that of the control group. The prevalence of cardiogenic shock (RR = 0.33%, 95% CI [0.11–1.04]) was p > 0.05, and the difference was not statistically significant. There was no statistically significant difference in LVEF between the two groups (MD = 0.00%, 95% CI [0.00–0.00]). CK-MB (MD = −0.81%, 95% CI [−0.92∼ −0.69]) was lower than the control group. hs-CRP (MD = −1.09, 95% CI [−1.22∼ −0.97]) was lower than the control group. The incidence of adverse reactions (RR = 0.37, The 95% CI [0.17–0.82]) was lower than that in the control group. Conclusion Basing on our study, the use of DHI in the treatment of myocardial infarction patients is effective, can improve cardiac function, reduce the incidence of adverse reactions, and improve the overall quality of life. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023390973.